Gaze and motor behavior of people with PD during obstacle circumvention - Simieli, Lucas [UNESP] (2017)
The aim of this study was to analyze the motor and visual strategies used when walking around (circumvention) an obstacle in patients with Parkinson's disease (PD), in addition to the effects of dopaminergic medication on these strategies. To answer the study question, people with PD (15) and neurologically healthy individuals (15-CG) performed the task of obstacle circumvention during walking (5 trials of unobstructed walking and obstacle circumvention). The following parameters were analyzed: body clearance (longer mediolateral distance during obstacle circumvention of the center of mass-CoM-to the obstacle), horizontal distance (distance of the CoM at the beginning of obstacle circumvention to the obstacle), circumvention strategy (lead-out or lead-in strategy), spatial-temporal of each step, and number of fixations, the mean duration of the fixations and time of fixations according to areas of interest. In addition, the variability of each parameter was calculated. The results indicated that people with PD and the CG presented similar obstacle circumvention strategies (no differences between groups for body clearance, horizontal distance to obstacle, or obstacle circumvention strategy), but the groups used different adjustments to perform these strategies (people with PD performed adjustments during both the approach and circumvention steps and presented greater visual dependence on the obstacle; the CG adjusted only the final step before obstacle circumvention). Moreover, without dopaminergic medication, people with PD reduced body clearance and increased the use of a lead-out strategy, variability in spatial-temporal parameters, and dependency on obstacle information, increasing the risk of contact with the obstacle during circumvention.